Beyond orchestration: Norm perspective in technology integration - (:unkn) unknown (CHARLES UNIV, FAC EDUC, 2015)
The aim of this study is to bring a socio-cultural dimension to instrumental orchestration framework. Our claim is that social and socio-mathematical norms endorsed by teachers are crucial for their pedagogies. A case study was designed to investigate how orchestration types and norms affect each other in technology-enhanced learning environments. Participants are five pre-service mathematics teachers. Data were collected through lesson plans, semi-structured interviews and observations. Analysis of data indicates that there is a two-way interaction between norms and orchestration types. In some cases, norms are determinants of orchestration types used by participants. In other cases, orchestration types challenge participants' endorsed norms.
Keywords: Socio-cultural approach; Social norm; Socio-mathematical norm; Instrumental orchestration